Understanding dentists’ caries management: The COM-B ICCMS™ questionnaire (2018)
Objective To design and validate a questionnaire to measure caries management based on the Capability, Opportunity, and Motivation Behavior model (COM‐B) and the International Caries Classification and Management System (ICCMS™). Methods A combination of Cariology and Psychology experts developed a 79‐item pool that measured the COM‐B components according to the ICCMS™ caries management recommended behaviours. After face and content validation and a pilot study, two samples of Colombian dentists participated: clinicians (n = 277) and clinical‐practice educators (n = 212). Results Using parallel analysis and exploratory structural equation modelling (ESEM), the questionnaire was reduced to a 47‐item 5‐factor instrument that demonstrated good internal consistency and validity properties, including a robust factor structure, measurement invariance across samples and high predictive validity of ICCMS™ recommended behaviours. Scales’ mean scores showed that dentists were conducting recommended behaviours “most‐of‐the‐time” (Behavior), showed high confidence in their ability to conduct these behaviours (Capability) and considered recommendations as highly relevant (Opportunity‐Relevance), while their appraisals of the available resources (Opportunity‐Resources) and remuneration (Motivation) were notably lower. Conclusion Overall, the findings highlight the practical utility of the COM‐B ICCMS™ Questionnaire in understanding the potential antecedent variables that may explain dentists’ behaviours related to caries diagnosis and management and in suggesting avenues for achieving a positive change in their behaviour.